Synthesis and Pharmacological Evaluation of a Novel Series of Cyclopentenone Derivatives. (January 2017) - El-Samahy, Fatma A.; El-Hussieny, Marwa; El-Sayed, Naglaa F.; Shalaby, Elsayed M.; Osman, Fayez H.
A novel series of cyclopent-2-enone derivatives have been synthesised by the reaction of 4-hydroxy-3, 4-diphenylcyclopent-2-enone, cyclic secondary amines, phosphorus reagents, hexamethylphosphoramide and Lawesson's reagent in boiling toluene/THF. The chemical structures of new compounds were identified by 1 H NMR, 13 C NMR, 31 P NMR and mass spectra. Furthermore, the structure of one of the synthesised compounds has been confirmed using single crystal X-ray diffraction. The pharmacological evaluation results of antilung and anticolon carcinoma cell line properties for the products are discussed.